Trends and Opportunities of Rapid Prototyping Technologies - Păcurar, Răzvan (IntechOpen, 2022)
Trends and Opportunities of Rapid Prototyping Technologies provides a comprehensive overview of rapid prototyping, also known as 3D printing. It discusses challenges in this domain, such as lack of standardization and certification, as well as the requirements coming from the industrial sector. The book examines existing 3D printing methods and materials as well as their applications, customizations, and process parameters.